2021
DOI: 10.1111/anu.13311
|View full text |Cite
|
Sign up to set email alerts
|

Adaptations of hepatic lipid and glucose metabolism in response to high‐macronutrient diets in juvenile grass carp

Abstract: The persistent overfeeding of high-energy feed is one of the farming technology to achieve fast growth in a relatively short period, but also is one of the reasons that the cultured fish are fatter or produce greater visceral mass than the wildfish (Du et al., 2008;

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 51 publications
3
3
0
Order By: Relevance
“…In this study, the liver glycogen contents in HS group were significantly higher than those in LS group, which is consistent with previous reports in common snook (Centropomus undecimalis) (Arenas et al, 2021), Chinese perch (Siniperca chuatsi) (Zhang et al, 2021a) and juvenile grass carp (Xie et al, 2021).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In this study, the liver glycogen contents in HS group were significantly higher than those in LS group, which is consistent with previous reports in common snook (Centropomus undecimalis) (Arenas et al, 2021), Chinese perch (Siniperca chuatsi) (Zhang et al, 2021a) and juvenile grass carp (Xie et al, 2021).…”
Section: Discussionsupporting
confidence: 92%
“…Previous studies reported that the increase in carbohydrates in the feed also led to the increase in glycogen contents in the liver (Arenas et al, 2021; Moreira et al, 2008). In this study, the liver glycogen contents in HS group were significantly higher than those in LS group, which is consistent with previous reports in common snook ( Centropomus undecimalis ) (Arenas et al, 2021), Chinese perch ( Siniperca chuatsi ) (Zhang et al, 2021a) and juvenile grass carp (Xie et al, 2021).…”
Section: Discussionsupporting
confidence: 92%
“…Generally, elevated plasma glucose levels to high carbohydrate consumption may enhance glycolysis coupled with suppression of gluconeogenesis [42]. In the present study, two key genes involved in the gluconeogenesis pathway are significantly decreased in the liver of zebrafish when fed excess dietary carbohydrates (30%-50% dextrin), and this result is similar to that in grass carp [43] and gibel carp [41]. These in vivo results are consistent with the results in ZFL when incubated in high glucose.…”
Section: Discussionsupporting
confidence: 90%
“…Therefore, high-fat feed is widely used in fish farming. However, recent studies have indicated that the intake of high fat diet (HFD) often induces excess fat deposition, metabolic disorders, and immune dysfunction (Jin et al, 2013;Lu et al, 2014;Xie et al, 2021a;Yin et al, 2021).…”
Section: Introductionmentioning
confidence: 99%